The relationship between bone marrow activity detected on PET / CT and prognosis in patients with lymphoma (Annals of Medical Research, 2021)
Aim: In this study, we aimed to evaluate the relationship between survival of patients with lymphoma who were considered to be negative for bone marrow (BM) infiltration and BM FDG uptake on PET / CT.Material and Methods: This retrospective study included 55 patients diagnosed with lymphoma (33 HL and 22 NHL), with no BM infiltration (by biopsy or clinically negative) and having pre-treatment PET / CT. According to the pattern of BM FDG uptake on PET / CT the patients were divided into three groups as; those with focal FDG uptake (F-FDG), those with diffuse increased FDG uptake (D-FDG) and those with normal FDG uptake (N-FDG). The overall survival (OS) and progression-free survival (PFS) curves of the patients were plotted with Kaplan Meier method. The OS and PS of patients who were grouped according to the pattern of BM FDG uptake on PET / CT, gender, disease stage and lymphoma type were compared with Log Rank test.Results: The mean follow-up period of our study was 23.7 ± 2.1 months (1-53 months). The mean OS was 41.9 ± 2.8 months, and the mean PFS was 37.8 ± 3 months. Ten patients showed focal or multifocal FDG uptake of BM on PET / CT (F-FDG). 28 patients had diffuse increased FDG uptake in the BM (D-FDG). In 17 patients, BM FDG uptake was within normal limits (N-FDG). There was no significant difference between OS and PFS of patients grouped according to gender, stage of disease, type of lymphoma and BM FDG uptake pattern (p> 0.05). Older age was associated with shorter OS and PFS.Conclusion: In our study, no significant relationship was found between BM FDG uptake on PET / CT and survival of patients with lymphoma with negative BM infiltration. However, although PET / CT does not completely replace BM biopsy, it may be helpful in detecting early infiltration of BM.
Keywords: Lymphoma; bone marrow; FDG; PET/CT